Stakeholder disconnect: Differences between farmers, extension workers, and researchers on preferred strategies for timely wheat sowing in Bihar, India - Gupta, Shweta; Kishore, Avinash; Burton, Michael (International Food Policy Research Institute, 2025)
Late sowing of wheat is a persistent problem in South Asia despite widespread awareness that it lowers crop yields. We asked 2034 farmers, 33 researchers, and 114 frontline extension workers (EW) in Bihar, India to rank 6 commonly recommended solutions for their effectiveness. Respondents faced repeated rounds of best-worst choices to obtain a full ranking of the options. Responses were analyzed using random utility models. Farmers ranked timely and affordable irrigation as the most effective solution and zero-tillage (ZT) the least effective one; researchers ranked ZT the highest. The EW were somewhere in the middle. A better understanding of the reasons behind the differences in the assessments of researchers, extension personnel, and farmers about what will work the best will generate better solutions.